Coagulation induced by C3aR-dependent NETosis drives protumorigenic neutrophils during small intestinal tumorigenesis - Silvia Guglietta (Nature Portfolio, 2016)
It is unclear whether cancer-related hypercoagulation and neutrophilia contribute to tumorigenesis. In this study, the authors find that activation of the complement cascade causes hypercoagulation that leads to polarization of neutrophils in a mouse model of intestinal cancer, and show that blocking complement activation can reduce tumour formation.